CHARACTERS OF THE MAIN CHARACTERS IN THE NOVEL HILDA: CINTA, LUKA, DAN PERJUANGAN BY MUYASSAROTUL HAFIDZOH - Fira Yuniar; Irianto Ibrahim; Andi Muhammad Ruum Sya'baan (CASA CENDEKIA MEDIA, 2026)
This study aims to analyze the characterization of the protagonist in the novel Hilda: Cinta, Luka, dan Perjuangan by Muyassarotul Hafidzoh through a literary psychology perspective. The novel portrays the life of a female protagonist who experiences sexual violence, social stigma, and gender-based injustice, resulting in complex psychological conflicts. This research employs a qualitative descriptive method with a library research design. The primary data source is the novel itself, while the data consist of textual excerpts in the form of narration, dialogue, and character behavior related to the protagonist’s psychological condition. Data were collected through close reading and note-taking techniques and analyzed using a literary psychology approach that focuses on internal conflict, emotional responses, and character development. The findings reveal that Hilda is depicted as a dynamic character whose personality develops through stages of trauma, inner struggle, and resilience. Initially, she is portrayed as fragile, fearful, and oppressed due to the psychological impact of sexual violence and social ostracization. However, as the story progresses, Hilda demonstrates psychological endurance, responsibility, and self-awareness, indicating a gradual transformation into a stronger and more resilient individual. This character development reflects the interaction between personal trauma and external social pressures. This study concludes that the protagonist in Hilda: Cinta, Luka, dan Perjuangan represents a female character who is not merely a victim of violence and injustice but also an active subject who struggles to survive and reconstruct her identity. The research contributes to Indonesian literary studies by offering a deeper understanding of female protagonists through the integration of psychological dynamics and social context, and it also provides relevant insights for literature learning and character education.